Digital transformation and museums without borders A evaluation of seven museums of Lima city in pandemic times - Pino Apablaza, Fernando (2021)
The research was descriptive. Had like objective, know the usage levels about digital technologies of seven importants museums of Lima city. Were considered two thechnological dimensions. One that was called digital technologies in situ, because its are within the fisical space of museum, and the other dimensión called digital technologies via remote, wich are, give access from the space outside the museum. Also show a short theoretical framework, that describe how the liquid society diluted in plenty digital revolution. The hypothesis indicate a low level about the usage of digital technologies in the museums of Historic Center of Lima. The results were moderate, showing frugality by museums in cumthe usage of digital technologies. In conclusion, in the most importante museums of Lima  city, exist digital gaps yet for remedy. The economy is a limiting factor in the digitization of museums and exist yet reticences and lethargy to board the digital transformation.